Challenges and Readiness of VR and AI Integration in STEM-based Mathematics Education: A Case of Urban and Rural High Schools - Cindy Indra Amirul Fiqri; Yus Mochamad Cholily; Mohammad Syaifuddin; Moh. Mahfud Effendi; Abdulkadir Rahardjanto (Didaktik Matematika, 2025)
The integration of Virtual Reality (VR) and Artificial Intelligence (AI) in STEM-based mathematics learning offers significant potential to enhance students' comprehension of abstract concepts. This study aims to identify key infrastructure and technology readiness challenges and propose practical solutions. Using a qualitative research design, data were collected through in-depth interviews with ten teachers and 85 students from secondary schools and analyzed thematically. The results highlight three primary barriers: limited internet access, high hardware costs, and insufficient technical training. While students showed enthusiasm toward VR and AI, teachers expressed a lack of preparedness to utilize these technologies. Furthermore, the digital divide between urban and rural schools aggravates educational inequities. To address these challenges, the study recommends increased investment in digital infrastructure, provision of hardware subsidies, and continuous teacher training programs. Collaboration between the government and private sector is also essential to bridge gaps and support the effective implementation of VR and AI in education. This research contributes by offering insights and actionable strategies for integrating emerging technologies in STEM education, ultimately improving learning outcomes and reducing educational disparities.